High-Risk Terrorism Inmate Deradicalization: A Complex and Paradoxical Issue in Nusakambangan - Siregar, Rahmat Amin (Jurnal Kriminologi Indonesia, 2025)
Deradicalizing high-risk terrorism inmates is a multifaceted and paradoxical challenge that has not been comprehensively addressed in criminological studies. This research seeks to fill the gaps in previous studies by focusing on the security challenges, personnel difficulties, and prison culture dynamics within super-maximum security facilities in their efforts to deradicalize terrorism inmates. The findings highlight three critical aspects of this complexity. First, the security measures in super-maximum security facilities emphasize the strict implementation of a one-inmate-per-cell system, which minimizes inmate interactions, adheres to high-security standards, and utilizes advanced technological systems. Second, correctional officers face significant challenges, including verbal confrontations from inmates, the harsh environmental conditions of Nusakambangan Island, the need for strong mental resilience, limited human resources, and constraints in the execution of interagency programs for deradicalization. Third, the prison culture of terrorism inmates in Nusakambangan’s super-maximum security facilities is characterized by radicalism dissemination patterns, inmate categorization, deterrent experiences, recidivism in radical behavior, and the daily habits of inmates within their cells. This study highlights the importance of future research that evaluates and compares deradicalization processes across various correctional facilities in Indonesia, with the goal of developing a more comprehensive understanding of this critical issue.